DAMPAK LITERASI PADA KEMAMPUAN BERKOMUNIKASI: TINJAUAN LITERATUR KETERAMPILAN MEMBACA BAHASA INDONESIA - Rahmawati, Siti; Sarwi, Sarwi; Sudarmin, Sudarmin (Elementar : Jurnal Pendidikan Dasar, 2024)
Reading skills are a competency that students must have. Reading is a skill that can be a supporting factor in other language skills such as speaking and writing. Through the habit of reading, of course, it increases students' knowledge. With increasing knowledge, of course, students' communication skills can also develop well, because the habit of reading makes students have a high curiosity. The purpose of this study is to review the impact of literacy on communication skills. This study uses the literature review method. 10 articles were obtained that were in accordance with the objectives of the literature review. This literature review was synthesized using the narrative method by grouping similar extracted data according to the results measured to answer the objectives. The results of the literature review of 10 relevant articles show that this literacy has a great influence on students' communication skills. Literacy is an important foundation in education and everyday life.